SUBSTANTIATION OF OPTIMIZED FORMULA AND TECHNOLOGICAL SCHEME OF OBTAINING GLUTEN-FREE BREAD WITH SEEDS MUNG BEAN AND CHIA - I. N. Pushmina; V. N. Orobinskaya; O. Ya. Kolman; I. S. Deibert (Современная наука и инновации)
The article presents the rationale for a new optimized recipe and technological scheme for the production of gluten-free bread with the addition of seeds mung bean and chia. An assessment of the quality and safety indicators of new gluten-free bread with seeds mung bean and chia is given, its compliance with the requirements of current regulations and standards is confirmed, and the prospects for creating recipes for gluten-free bakery products of increased nutritional value with the addition of non-traditional vegetable raw materials - seeds mung bean and chia are shown.